2001
DOI: 10.1046/j.1442-2042.2001.00373.x
|View full text |Cite
|
Sign up to set email alerts
|

Transitional cell carcinoma of the renal pelvis forming tumor thrombus in the vena cava

Abstract: A 47-year-old man presented with a left renal incidentaloma without hematuria. The tumor was complicated by inferior vena cava (IVC) thrombus extending from Th 11 to L 4 . A temporary IVC filter was introduced prior to surgery. A midline incision was used to perform a left radical nephrectomy and en bloc lymphadenectomy with excision of the inferior vena cava from above the level of the left renal vein to 2.5 cm above the confluence of the common iliac veins. The pathological diagnosis was invasive transitiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Eight died of the disease within 6 months of surgery. In another review of cases done in 2005, 13 reported cases of renal pelvic sarcomatoid carcinoma had been documented since 1961, and all patients presented with metastatic disease or advanced renal parenchymal involvement, with a mean survival time of less than 9 months [8]. A normally thin renal pelvic musculature supports the extension of the tumor to contiguous structures like the renal parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Eight died of the disease within 6 months of surgery. In another review of cases done in 2005, 13 reported cases of renal pelvic sarcomatoid carcinoma had been documented since 1961, and all patients presented with metastatic disease or advanced renal parenchymal involvement, with a mean survival time of less than 9 months [8]. A normally thin renal pelvic musculature supports the extension of the tumor to contiguous structures like the renal parenchyma.…”
Section: Discussionmentioning
confidence: 99%
“…Urinary cytological analysis was reported to have a diagnostic accuracy of 59%, but with a high ratio of false negatives for malignancy (5). A CT scan finding of preserved reniform kidney shape by an infiltrating neoplastic process supports the diagnosis of UC (2). In addition to CT and magnetic resonance urography, flexible ureteroscopy techniques, fluorescent in situ hybridization and narrow-band imaging may also facilitate diagnosis, and have thus been widely accepted (6).…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, aggressive surgery for the removal of an IVC thrombus proven beneficial for patients with RCC; however, its value in the management of renal UC remains unclear, due to limited data and the aggressive nature of UC (1,2). Existing data indicates that patients who present with UC and an IVC tumor thrombus have a poor prognosis, despite aggressive radical nephrectomy or nephroureterectomy, as the majority of patients succumbed within 6 months of the initial diagnosis (2). Although no benefits of surgery have been reported in such advanced cases of UC (6), surgical intervention may serve as a palliative treatment option or as a means to decrease the risk of thrombus shedding, as in the present case.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 20% had a positive cytology and all patients, in whom a retrograde pyelography was performed, demonstrated a renal pelvic/ureteral filling defect. In 60% of cases, nephrectomy without ureterectomy was performed and average survival was 6 months (17,18). Renal UC has a propensity to recur in the ipsilateral ureter at a rate of 30 to 40% and mandates radical nephroureterectomy (19,20).…”
Section: Commentsmentioning
confidence: 99%